2013
DOI: 10.1016/j.jvs.2012.08.107
|View full text |Cite
|
Sign up to set email alerts
|

The risk of carotid artery stenting compared with carotid endarterectomy is greatest in patients treated within 7 days of symptoms

Abstract: The increase in risk of CAS compared with CEA appears to be greatest in patients treated within 7 days of symptoms. Early surgery might remain most effective in stroke prevention in patients with symptomatic carotid artery stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(63 citation statements)
references
References 27 publications
3
60
0
Order By: Relevance
“…22 In addition, another single-center trial and a subgroup analysis by guest on May 7, 2018 http://stroke.ahajournals.org/ Downloaded from of the Carotid Stenosis Trialists' Collaboration data performed multivariable regression analyses comparing patients treated within 7 days after the index event with patients treated later. 23,24 In accordance with the present analysis, neither study found any significant association between the time interval and the 30-day risk of any stroke or death. In contrast, the Swedish register study by Strömberg et al 10 found a significantly increased perioperative risk of stroke or death when the procedure was performed within the first 2 days after the index event.…”
Section: Discussionsupporting
confidence: 88%
“…22 In addition, another single-center trial and a subgroup analysis by guest on May 7, 2018 http://stroke.ahajournals.org/ Downloaded from of the Carotid Stenosis Trialists' Collaboration data performed multivariable regression analyses comparing patients treated within 7 days after the index event with patients treated later. 23,24 In accordance with the present analysis, neither study found any significant association between the time interval and the 30-day risk of any stroke or death. In contrast, the Swedish register study by Strömberg et al 10 found a significantly increased perioperative risk of stroke or death when the procedure was performed within the first 2 days after the index event.…”
Section: Discussionsupporting
confidence: 88%
“…However, postprocedure morbidity and mortality in both treatment arms were high enough to call into question the benefit of either procedure compared with medical management in asymptomatic patients. 358,359 Other RCTs, the EVA-3S (Endarterectomy Versus Angioplasty in Patients With Symptomatic Severe Carotid Stenosis), SPACE (Stent-Supported Percutaneous Angioplasty of the Carotid Artery versus Endarterectomy), and ICSS (International Carotid Stenting Study) trials, have compared CEA and CAS for symptomatic patients. 360 A preplanned meta-analysis of these studies found that the rate of stroke and death at 120 day after randomization was 8.9% for CAS and 5.8% for CEA (HR, 1.53; 95% CI, 1.20-1.95; P=0.0006).…”
mentioning
confidence: 99%
“…In their study, Rantner et al determined that the risk of CAS, in comparison with CEA, is greatest in patients treated within 7 days of the symptoms. Accordingly early surgery remains the most effective method for stroke prevention in patients with symptomatic carotid artery stenosis (21) . Park et al determined a statistically significant reduction in the length of hospitalization in CAS as against CEA (1.2 vs. 2.1 days), while CAS turned out to be associated with higher total procedural costs ($17.402 vs. $12.112; p<0.029) and direct costs ($10.522 vs. $7227; p<0.017).…”
Section: Discussionmentioning
confidence: 99%